Determinan Gangguan Fungsi Kognitif Penderita Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Ciracas - Vinna Fazrihardani Adlis; Tri Budi Wahyuni Rahardjo; Atik Kridawati (LPPM Universitas Respati Indonesia, 2026)
Cognitive impairment among patients with Type 2 Diabetes Mellitus (T2DM) poses a growing public health challenge, especially amidst increasing life expectancy and diabetes prevalence. This condition can impact patients' quality of life and adherence to disease management. This study aims to analyze the determinants of cognitive impairment in T2DM patients at the Ciracas Primary Health Center. This is a quantitative study with a cross-sectional design. A total of 295 respondents were selected using Non-Random Sampling with the Accidental-Quota Sampling technique. Cognitive function was assessed using the MMSE, and data were analyzed using chi-square tests for bivariate analysis and logistic regression for multivariate analysis. The study found that age (p=0.04), education level (p=0.000), HbA1c level (p=0.008), and history of hypertension (p=0.002) were significantly associated with cognitive impairment in T2DM patients. In contrast, gender, duration of diabetes, and cholesterol levels showed no significant relationship. The most strongly associated statistically was a history of hypertension.Most patients with cognitive impairment were elderly and low-educated, had uncontrolled HbA1c levels, and had a history of hypertension. It is recommended that cognitive assessments be integrated into primary healthcare programs like PROLANIS for more comprehensive T2DM management